Reduced Order Model for Two Areas to Represent Coherent Groups in Power Electric Systems - Chavez-Orostica, H; Quiroz-Moreno, J; Barrueto-Guzman, A (Institute of Electrical and Electronics Engineers Inc., 2022)
The analysis of the frequency response of multi-area power systems is a complex and intensive task in the use of computational resources. This paper considers the implementation of a reduced model to represent coherent groups in a two area power system and the tuning of a synchronization coefficient, that represents the equivalent tie line. This work provides a basis for future analysis of more complex power systems, with three or more coherent areas. © 2022 IEEE.